2021
DOI: 10.3390/su13179795
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Public University of Navarre in Achieving the 1st SDG for the End of Poverty

Abstract: The end of poverty is the first of the 17 sustainable development goals of the United Nations. Universities are strategic spaces for promoting the SDGs, from training, research, and outreach capacity to implementing sustainable actions, helping to reduce inequalities and, significantly, promoting sustainable cities and communities. This article aims to answer how the Public University of Navarre contributes to promoting the 1st SDG, what mechanisms for the end of poverty endorses in its territory, and what can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…Policies related to sustainability in higher education should be coherent and aligned with broader sustainability goals and frameworks, such as the SDGs [127]. Universities should align their sustainability strategies and initiatives with the SDGs to ensure a comprehensive and integrated approach to sustainability [128]. Adequate funding is essential to support sustainability initiatives in higher education institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Policies related to sustainability in higher education should be coherent and aligned with broader sustainability goals and frameworks, such as the SDGs [127]. Universities should align their sustainability strategies and initiatives with the SDGs to ensure a comprehensive and integrated approach to sustainability [128]. Adequate funding is essential to support sustainability initiatives in higher education institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Entendiendo que la disposición hacia el desarrollo del pensamiento crítico es fundamental (As'ari et al, 2017;Facione & Facione, 1992), es necesario identificar los factores que determinan el grado de motivación del alumnado para aprender dichas habilidades. Debido a la realidad social que vivimos actualmente, caracterizada por retos y problemáticas globales que afectan al medio ambiente, a la sociedad y a la economía, el pensamiento crítico cobra especial relevancia (Changwong et al, 2018;Martínez-Virto & Pérez-Eransus. 2021;Sagun et al, 2016).…”
Section: V-discusiónunclassified
“…La universidad como institución innovadora, creadora y difusora de nuevos conocimientos desempeña un rol fundamental para contribuir a resolver los problemas globales (Martínez-Virto & Pérez-Eransus, 2021;Sánchez et al, 2017). Por ello, debe asumir un papel de liderazgo para propiciar el cambio hacia sociedades más justas y sostenibles.…”
Section: I-introducciónunclassified
“…Karlsen et al (2019) concluded that unless universities combine different circumstances (homogeneous & heterogeneous), the development of socially responsible teaching and research missions has no potential. In that case, Martínez-Virto and Pérez-Eransus ( 2021 ) empirically researched three manners in which one of the public university in Navarre (Spain) contributed to the United Nations’ first Sustainable Development Goal (SDG1). First, in regard to teaching, the university introduced professional training courses on bachelor and master’s levels in the field of poverty, developed specific cross-cutting SDG1 trainings, and launched different professional networks in collaboration with stakeholders and patterners to end poverty.…”
Section: Introductionmentioning
confidence: 99%